Sequential Hybrid Surgical CryoMaze and Transvenous Catheter Ablation of Atrial Fibrillation - Eisenberger, Martin; Bulava, Alan; Mokracek, Ales; Hanis, Jiri; Kurfirst, Vojtech; Dusek, Ladislav (Pacing and clinical electrophysiology, 2015)
BACKGROUND: The aim of the study was to evaluate whether the sequential hybrid approach combining surgical CryoMaze followed by the radiofrequency (RF) catheter ablation can improve freedom from atrial arrhythmias. METHODS: Thirty-five patients with persistent atrial fibrillation underwent a CryoMaze procedure in conjunction with cardiac surgery for structural heart disease. Three months after surgery, all patients underwent a 7-day electrocardiogram Holter followed by an electrophysiological study and mapping of the left and right atria. All pulmonary veins were reisolated and all ablation lines were completed, if necessary, using RF energy. Patients were followed-up at 3 months, 6 months, and 12 months after the catheter ablation. RESULTS: Before the mapping study and RF ablation, nine patients (26%) had ongoing atrial fibrillation or atrial tachycardia, 10 patients (28%) had paroxysmal atrial tachyarrhythmia, and 16 patients (46%) had sinus rhythm on the 7-day Holter monitoring. During the electrophysiological procedure, complete cryoablation lines around the left pulmonary veins were found in 29 patients (83%), around the right pulmonary veins in 25 patients (71%), between the superior veins in 20 patients (57%), between the inferior veins in 27 patients (77%), across the mitral isthmus in 12 patients (34%), and across the cavotricuspid isthmus in one patient (3%). Arrhythmia-free survival rate of antiarrhythmic drugs after reisolation of the veins and completion of the lines was 86% at 12 months. CONCLUSION: Ablation lines created using surgical CryoMaze are often incomplete. Sequential surgical CryoMaze procedures followed by catheter ablation significantly increase freedom from arrhythmia in patients with persistent atrial fibrillation.
Keywords: výsledek terapie; kombinovaná terapie; CryoMaze; Cardiac Surgical Procedures; Cryosurgery; Male; Combined Modality Therapy; atrial fibrillation; catheter ablation; Aged; mužské pohlaví; senioři; Catheter Ablation; surgical ablation; Atrial Fibrillation; Pulmonary Veins; Treatment Outcome; lidé; ženské pohlaví; Humans; incomplete lines; kryochirurgie; venae pulmonales; hybrid approach; katetrizační ablace; Female; kardiochirurgické výkony; fibrilace síní